Analytical Hierarchy Process at Supply Chain Management of Efficient Shallots (Case Study at Medan Main Market, North Sumatera) - Megawati Citra Alam (Faculty of Agriculture, Merdeka University Surabaya, 2020)
This research aims to identify and analyze roles, actors and alternative scenarios to form an efficient supply chain management of shallots in the Medan Main Market. The sample in this study were five respondents with judgment sampling method. The data taken in this research is primary data which is distributed directly to respondents. The results of baking data were analyzed using expert choice 11 software to identify and analyze roles, actors and alternative scenarios in forming efficient onion supply chain management in Medan City Main Market. The results of the analysis show that the product availability factor is the most determining factor in establishing efficient supply chain management of shallots. The actors who are considered to have the most role on the distributor side in the availability of products and achieving the goals of the producers' business sustainability are collectors. In achieving the objective of producing business sustainability, the alternative scenario chosen is government policy.